2012
DOI: 10.1080/09603123.2011.628792
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and pattern of arsenic concentration in drinking water wells in Córdoba, Argentina

Abstract: Cancer occurrence is associated with Arsenic (As) in drinking water. In Argentina, there are high As concentrations in groundwater but there is no published evidence yet of an association between geographic patterns of cancer incidence and the distribution of As in groundwater supplies. The purpose of this study is to assess the association between cancer incidence patterns and As in Córdoba province's aquifers. Age standardized incidence rates (ASIRs) were obtained from Córdoba Cancer Registry (CCR), and As d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Among the papers identifying cancer risk factors, we wish to highlight the following: i) the association between arsenic concentration in drinkable water and colon, lung and bladder cancer's incidence risk increase in Cordoba, Argentina (Aballay et al, 2012); ii) a relation between higher incidence and mortality rates by cervical cancer, and more poverty and/or higher distance to screening in USA (Horner et al, 2011); iii) the urban disadvantage in risk of breast, colorectal, lung and prostate cancers in Illinois (McLafferty and Wang, 2009); or iv) a relation between Vitamin D insufficiency and an increase of prostate cancer risk (Schwartz and Hanchette, 2006); v) a possible association among coal mining activities and cancer mortality in West Virginia (Hendryx et al, 2010).…”
Section: Methods Appliedmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the papers identifying cancer risk factors, we wish to highlight the following: i) the association between arsenic concentration in drinkable water and colon, lung and bladder cancer's incidence risk increase in Cordoba, Argentina (Aballay et al, 2012); ii) a relation between higher incidence and mortality rates by cervical cancer, and more poverty and/or higher distance to screening in USA (Horner et al, 2011); iii) the urban disadvantage in risk of breast, colorectal, lung and prostate cancers in Illinois (McLafferty and Wang, 2009); or iv) a relation between Vitamin D insufficiency and an increase of prostate cancer risk (Schwartz and Hanchette, 2006); v) a possible association among coal mining activities and cancer mortality in West Virginia (Hendryx et al, 2010).…”
Section: Methods Appliedmentioning
confidence: 99%
“…Individual data Cancer registries Aballay et al (2012), Absalon and Slesak (2011), Al-Ahmadi and Al-Zahrani (2013), Alvarez et al (2009), Bailony et al (2011), Bambhroliya et al (2012, Bristow et al (2014), Buntinx et al (2003), Cassetti et al (2008), Chen et al (2008b, 2011, Chien et al (2013a), Christian et al (2011), Colak et al (2015, Colonna (2004Colonna ( , 2006, Colonna et al (1990), Cramb et al (2011), Dai and Oyana (2008), David et al (2002), DeChello and Sheehan (2007), DeChello et al (2006), Drapeau et al (1995), Elebead et al (2012), Elferink et al (2012), Fairley et al (2008), Fedewa et al (2009), Ferreira et al (2012, Fortunato et al (2011), Gallagher et al (2010, Garcia Martinez et al (2014), Gbary et al (1995), Goodman et al (2010), Xiao (2011, 2012), Guajardo and Oyana (2009), Samociuk (2003, 2013) Godon et al (1991), Goovaerts (2005Goovaerts ( , 2006aGoovaerts ( , 2006b), Hendryx et al (2010), Hosseintabar Marzoni et al (2015, …”
Section: Data Type Source Articlementioning
confidence: 99%
“…7 In a study conducted in Argentina, correlations between high arsenic levels and lung, bladder, and colon cancers in females were found. 27 In another study conducted in Taiwan, it was found out that lung and bladder cancer risks increased 2.27 (95% confidence interval: 1.44-3.58) and 7.80 (95% confidence interval: 2.64-23.1) times, respectively, in cases where arsenic levels exceed 300 μg/L in water. 28 Moreover, Ç elik et al 29 have shown a correlation between arsenic levels and cancer incidence and mortality in their systematic review on arsenic in drinking water supply and lung cancer.…”
Section: Commentmentioning
confidence: 99%
“…Most of the dose-response assessments in other countries also adopted the mean or median level in a study area to represent the exposure of all the residents of that area (Aballay et al, 2012;Baastrup et al, 2008;Ferreccio et al, 1998Ferreccio et al, , 2000Han et al, 2008;Hinwood et al, 1999;Hopenhayn-Rich et al, 1998;Lewis et al, 1999;Mostafa et al, 2008;Smith et al, 1998), but some of them failed to find an association between arsenic level in drinking water and lung cancer (Baastrup et al, 2008;Hinwood et al, 1999;Lewis et al, 1999). While the others observed associations between arsenic exposure and lung cancer, some did not find an increase in the risk below certain exposure level, indicating a non-linear doseresponse relationship (Ferreccio et al, 1998;Mostafa et al, 2008), and some observed the associations in men only, indicating a gender difference (Han et al, 2008).…”
Section: Introductionmentioning
confidence: 99%